2022
DOI: 10.48550/arxiv.2208.01081
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coalescing black hole binaries from globular clusters: mass distributions and comparison to gravitational wave data from GWTC-3

Abstract: We use our cluster population model, cBHBd, to explore the mass distribution of merging black hole binaries formed dynamically in globular clusters. We include in our models the effect of mass growth through hierarchical mergers and compare the resulting distributions to those inferred from the third gravitational wave transient catalogue. We find that none of our models can reproduce the peak at m 1 10M in the primary black hole mass distribution that is inferred from the data. This disfavours a scenario wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 69 publications
0
5
0
Order By: Relevance
“…The mass distributions from other channels, such as hierarchical formation (Askar et al 2017;Antonini et al 2019;Rodriguez et al 2019;Antonini & Gieles 2020;Fragione & Silk 2020), chemically homogeneous evolution (CHE; e.g., de Mink et al 2009;Mandel & de Mink 2016;Marchant et al 2016;Riley et al 2021), population III binaries (e.g., Marigo et al 2001;Belczynski et al 2004;Kinugawa et al 2014;Inayoshi et al 2017), and binaries merging in the disks of active galactic nuclei (e.g., Baruteau et al 2011;Bellovary et al 2016;Leigh et al 2018;Secunda et al 2019;Yang et al 2019;McKernan et al 2020) are expected to peak at masses above 20 M e . Antonini et al (2022) furthermore show that the globular cluster channel underpredicts the observed rate of BBH mergers at the low-mass end (around 10 M e ) by about two orders of magnitude. Less confusion about the dominant formation channel also makes the low-mass end one of the most promising sites to distinguish any astrophysical redshift evolution of the mass distribution from cosmological evolution (e.g., María Ezquiaga & Holz 2022).…”
Section: Introductionmentioning
confidence: 72%
“…The mass distributions from other channels, such as hierarchical formation (Askar et al 2017;Antonini et al 2019;Rodriguez et al 2019;Antonini & Gieles 2020;Fragione & Silk 2020), chemically homogeneous evolution (CHE; e.g., de Mink et al 2009;Mandel & de Mink 2016;Marchant et al 2016;Riley et al 2021), population III binaries (e.g., Marigo et al 2001;Belczynski et al 2004;Kinugawa et al 2014;Inayoshi et al 2017), and binaries merging in the disks of active galactic nuclei (e.g., Baruteau et al 2011;Bellovary et al 2016;Leigh et al 2018;Secunda et al 2019;Yang et al 2019;McKernan et al 2020) are expected to peak at masses above 20 M e . Antonini et al (2022) furthermore show that the globular cluster channel underpredicts the observed rate of BBH mergers at the low-mass end (around 10 M e ) by about two orders of magnitude. Less confusion about the dominant formation channel also makes the low-mass end one of the most promising sites to distinguish any astrophysical redshift evolution of the mass distribution from cosmological evolution (e.g., María Ezquiaga & Holz 2022).…”
Section: Introductionmentioning
confidence: 72%
“…This may be an indication that the stable mass transfer channel operates more efficiently than the traditional common envelope channel for generating merging BBHs. Though dynamical formation channels with low escape velocities, such as globular clusters, struggle to produce a global maximum at 10 M (Antonini et al 2022), dynamical environments with higher escape velocities may more readily produce merging BBHs with lower masses around 10 M due to the more prevalent lower-mass BHs preferentially remaining bound to these clusters following supernova kicks.…”
Section: Discussionmentioning
confidence: 99%
“…This may be an indication that the peak at 35 M is the result of another BBH formation channel (e.g. globular clusters, see Antonini et al 2022), or that stellar evolution models are missing particular ingredients that can shift the location of the pair instability gap (relaxing the assumption that the exploding stars are hydrogen-free, adjustments to convective overshooting, see e.g. Iorio et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Baruteau et al 2011;Bellovary et al 2016;Leigh et al 2018;Yang et al 2019;Secunda et al 2019;McKernan et al 2020) are expected to peak at masses above 20 M . Antonini et al (2022) furthermore show that the globular cluster channel under-predicts the observed rate of BBH mergers at the low mas end (around 10 M ) by about two orders of magnitude. Less confusion about the dominant formation channel also makes the low mass end one of the most promising sites to distinguish any astrophysical redshift evolution of the mass distribution from cosmological evolution (e.g.,…”
Section: Introductionmentioning
confidence: 73%